Increased Tuberculosis Incidence Due to Immunotherapy Based on PD-1 and PD-L1 Blockade: A Systematic Review and Meta-Analysis - Liu, Kewei; Wang, Dongpo; Yao, Cong; Qiao, Min; Li, Qing; Ren, Weicong; Li, Shanshan; Gao, Mengqiu; Pang, Yu (Frontiers in Immunology, 2022)
Objectives: In this study, we conducted a systematic review to determine tuberculosis (TB) incidence due to immunotherapy with programmed cell death protein-1 (PD-1)/PD ligand (PD-L1) blockade in cancer patients. Methods: We searched PubMed, Cochrance Library, Excerpt Medica Database (Embase), ClinicalTrials.gov, Chinese BioMedical Literature Database (CBM), China National Knowledge Infrastructure Database (CNKI), Wanfang and China Science and Technology Journal Database to identify studies between January 1, 2000 and April 30, 2021, on the reports of TB cases in patients treated with PD-1/PD-L1 blockade. Methodological quality of eligible studies was assessed, and random-effect model meta-analysis was performed to generate the pooled incidence estimate of TB cases in patients undergoing PD-1/PD-L1 therapy. Results: We initially identified 745 records, of which 27 studies ultimately met the inclusion criteria and were included in our meta-analysis. A total of 35 TB cases occurred among patients treated with PD-1/PD-L1 blockade. Nivolumab (51.4%) was the most frequently used PD-1/PD-L1 blockade for cancer treatment. In addition, pulmonary TB was the most common form of tuberculosis seen in 77.1% cases. Clinical outcomes were recorded in 18 patients, of whom 77.8% were cured or achieved remission, and 22.2% were died of TB. Pooled analysis determined that the TB rate in this population was 2,000 cases per 100,000 persons, and the estimated rate for TB associated with PD-1/PD-L1 blockade was 35 times higher than that in the general population. Conclusion: To conclude, our results demonstrate that the clinical use of PD-1/PD-L1 inhibitors significantly increases risk of TB reactivation. An extremely high mortality rate due to TB disease is noted in the patients with PD-1/PD-L1 blockade.